Coral reefs: The good and not so good news with future bright and dark spots for coral reefs through climate change. (7th June 2022) - Devlin, Michelle J.
Abstract : COMMENTARY ON Present and future bright and dark spots for coral reefs through climate change. This is a commentary on Sully et al., 2022, https://doi.org/10.1111/gcb.16083